Role of Long Noncoding RNAs and Circular RNAs in Nerve Regeneration - Yao, Chun; Yu, Bin (Frontiers in Molecular Neuroscience, 2019)
Nerve injuries are a common clinical problem and cause inconvenience in daily life. It is of great importance to get a full understanding of the biological processes and molecular mechanisms underlying nerve injury to find and target specific molecules in nerve regeneration. Numerous studies have shown that noncoding RNAs (ncRNAs) participate in diverse biological processes and diseases. Long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) are two major groups of ncRNAs, which attract growing attention. The expression of lncRNAs and circRNAs are altered following nerve injury and are associated with nerve regeneration. This review will give a brief introduction of the origins, characteristics and classifications of lncRNAs and circRNAs. We then summarize the current studies on lncRNAs and circRNAs following peripheral nerve injury and spinal cord injury. Typical lncRNAs and circRNAs are introduced to illustrate the diverse molecular mechanisms. In addition, we also discuss some issues to be addressed in future investigations on lncRNAs and circRNAs.